DETECTION OF VIABLE SALMONELLA TYPHI USING THREE PRIMER PAIRS SPESCIFIC TO INVA, IVAB, AND FLIC-D GENES - Phumkhachorn, Parichat; Rattanachaikunsopon, Pongsak (Emirates Journal of Food and Agriculture, 2017)
The detection of viable (clinically significant) Salmonella enterica subsp. enterica serovar Typhi in food is essential from clinical, epidemiological, and infection control perspective. In this study, a method for detection of viable S. Typhi was developed based on reverse transcription-multiplex PCR (RT-MPCR). Three primer pairs used in RT-MPCR were invA-f/invA-r, ivaB-f/ivaB-r and fliC-d-f/fliC-d-r that were specific to invA gene, ivaB region and fliC-d gene, respectively. Of all S. enterica serovars, only S. Typhi had all target DNA that was able to be amplified by all 3 primer pairs. When RNA extracted from S. Typhi was subjected to RT-MPCR, 3 DNA products with the sizes of 284, 599 and 763 were observed. This method was shown to specifically detect S. Typhi with the detection limit of 50 CFU in pure culture. Moreover, RT-MPCR was shown to be able to detect S. Typhi and to discriminate between viable and nonviable cells in food.